Optimization of in planta methodology for genome editing and transformation in Citrus - Khadgi, Archana; Sagawa, Cintia H. D.; Vernon, Corina; Mermaz, Benoit; Irish, Vivian F. (Frontiers in Plant Science, 2024)
Genetic transformation of many plant species relies on in vitro tissue culture-based approaches. This can be a labor-intensive process, requiring aseptic conditions and regenerating often recalcitrant species from tissue culture. Here, we have optimized an in planta transformation protocol to rapidly transform commercial citrus cultivars, bypassing the need for tissue culture. As a proof of concept, we used in planta transformation to introduce CRISPR/Cas9 constructs into Limoneira 8A Lisbon lemon and Pineapple sweet orange, cultivars that are challenging to transform with conventional techniques. Using our optimized protocol, the regeneration rate was significantly increased from 4.8% to over 95%, resulting in multiple geneedited lines in lemon. We also successfully recovered gene-edited Pineapple sweet orange lines using this protocol; the transformation efficiency for these cultivars ranged between 0.63% and 4.17%. Remarkably, these lines were obtained within three months, making this in planta protocol a rapid methodology to obtain transformed citrus plants. This approach can rapidly and effectively introduce key genetic changes into a wide variety of citrus cultivars.